Challenges in accountability in higher education (Revista Electrónica Calidad en la Educación Superior, 2022)
This article analyzes accountability and its expansion in academic systems. Based on bibliographic and documentary research, this paper highlights the two senses of accountability: the normative and the technocratic. The hegemony of the technocratic sense over the normative one has implications for the model of accountability that is consolidating and does not favor the intelligent accountability of higher education systems.
Keywords: Higher education; responsability; accountability; quality of education